Differential Regional Brain Spontaneous Activity in Subgroups of Mild Cognitive Impairment - Zhou, Qi-Hui; Wang, Kun; Zhang, Xiao-Ming; Wang, Li; Liu, Jiang-Hong (Frontiers in Human Neuroscience, 2020)
Background: Amnestic mild cognitive impairment (aMCI) is associated with a high conversion risk to Alzheimer's disease (AD). The aMCI patients may have only a memory deficit (single domain: sd-aMCI) or deficits in multiple cognitive domains (multiple domain: md-aMCI). However, the differences in intrinsic brain activity between the 2 types of aMCI remain unclear. Method: Thirty-two patients with sd-aMCI, 23 patients with md-aMCI, and 23 healthy controls (HCs) were included. Neuropsychological and resting-state fMRI data were acquired from each subject. We used the fractional amplitude of low-frequency fluctuation (fALFF) to characterize the intensity of spontaneous brain activity. The between-group differences were determined using analysis of covariance (ANCOVA) and post-hoc tests. Results: We found significantly higher fALFF in left-sided superior-to-middle frontal gyri and middle-to-inferior temporal gyri in sd-aMCI compared to both the md-aMCI and HCs. Conversely, a gradually decreased fALFF was found in the left inferior parietal lobe in md-aMCI, sd-aMCI, and HCs. The fALFF values in the left middle and inferior temporal gyri were significantly correlated with cognitive performances in aMCI patients. Conclusion: The gradual reduction in the left inferior parietal lobe from single to multiple domain aMCI suggest a functional defficiency underlying cognitive impairment, while increased activity in the left-sided frontal and temporal gyri in saMCI rather than maMCI might indicates functional compensation. This study showed differential functional profiles in the sd-aMCI and md-aMCI, which may be helpful for the prediction of their future conversion to AD.